The daily mean zero‐flux plane during soil‐controlled evaporation: A Green's function approach. Issue 12 (12th December 2014) - Brutsaert, Wilfried
Abstract: A solution is presented of the linearized Richards equation with inclusion of gravity and with appropriate boundary conditions describing the combined soil‐controlled surface evaporation and the downward infiltration, following the application of a given amount of precipitation or irrigation. This solution is shown to agree with available field measurements, namely the evolution with time of the zero‐flux plane depth and of the rate of soil‐controlled evaporation from the bare soil surface. The problem is solved by means of the Green's function method; the result is general enough to be also applicable to flow problems in linear soils with boundary conditions substantially different from the ones considered herein. Key Points: The zero‐flux plane depth remains relatively invariant during this process Daily mean evaporation from drying soil behaves like a linear diffusion process